Is Preoperative Planning for Hip Surgery Using Three-Dimensional Printed Models Associated with Improved Intra- and Postoperative Outcomes? A Systematic Review - Mosca, Michael J.; Castañeda, Pablo (The Journal of Hip Surgery, 2019)
Use of three-dimensional (3D) printed models for preoperative planning, patient-specific surgical guides, and implants in orthopaedic surgery is a burgeoning technology. It has not been established if 3D-printed models for preoperative planning are associated with improved clinical outcomes or if they are cost-effective for hip surgeries including total hip arthroplasty (THA), periacetabular osteotomy (PAO), proximal femoral osteotomy (PFO), and/or hip fractures. The purpose of this study was to conduct a systematic search and literature review to determine if preoperative planning for hip surgery using 3D-printed models was associated with improved intra- and postoperative outcomes. Specific aims were to determine the (1) types of applications and studies conducted, (2) types of 3D printing/materials used, (3) specific outcomes evaluated, (4) efficacy of 3D printing in planning for hip surgery, and (5) limitations of current research. The authors searched Medline, Embase, Cochrane Database of Systematic Reviews, CINAHL, and PubMed from inception through July 2017. Original research publications were included if the primary purpose was to evaluate 3D-printed models' ability to assist with the planning of hip surgeries. Papers were excluded if they were reviews, abstracts, and not available in English, their models were not patient-specific, or their research did not evaluate surgery of the acetabulofemoral joint or pelvis. Of the 3,369 unique papers identified, 21 met inclusion criteria after full-text review. Among the included studies, six evaluated 3D printing in THA, seven in PAO/PFO, and eight in fracture repairs/reconstruction. The research included nine case reports, three case series, one retrospective uncontrolled study, six prospective uncontrolled studies, and two prospective controlled studies. 3D printed models resulted in: reduced intraoperative improvisation, operating room time, blood loss/transfusions, improved positioning of plates/screws/implants, clinical scores, measures of realignment, and functional status. Recent innovations in 3D printing are promising but unproven to improve clinical outcomes in hip surgeries due to limitations of published research. This may impact utilization and reimbursement of 3D-printed models in hip surgery. Studies of resource utilization, cost-effectiveness, and controlled trials with standardized methods and clinical outcomes of relevance are needed.
Keywords: 3D printing; orthopaedics; arthroplasty; hip dysplasia; reviews